Hubungan Merokok Terhadap Keluhan Nyeri Punggung (Low Back Pain) pada Pekerja Pasukan Pemadam Kebakaran dan Penyelamatan di Dinas Pemadam Kebakaran dan Penyelamatan Kota Medan dalam Pendekatan Maqasid Syariah - Mayang Dwi Octavia; Irwansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the relationship between work posture and complaints of low back pain among fire and rescue officers at the Medan City Fire and Rescue Service. The method used was quantitative and qualitative through observation, questionnaires and interviews involving 95 officers. The results showed that there was a significant relationship between smoking habits and LBP complaints, with 34.7% of smoking officers experiencing these complaints. Apart from that, lack of attention to health, personal hygiene and consumption of unhealthy food in the work environment also contributes to this health problem. In the context of maqasid sharia, smoking and other unhealthy behaviors are considered detrimental and should be avoided. This research underlines the importance of an Islamic-based approach in increasing awareness of occupational safety and health, as well as the need for efforts to reduce smoking habits among officers.